Fabrication, Characterization and Testing composite films of Poly(vinyl) Alcohol (PVOH)/ hybrid materials for potential use in strawberry packaging. - Ruiz Madronero, Christhy; et al. (A Complete Guide to Hybrid Materials, 2020)
Hybrid materials based on layered zinc hydroxide salts and phenolic compounds were incorporated into the polymer matrix of polyvinyl alcohol (PVOH) as fillers to form composite films using casting method. The structural, thermal, morphologic and compositional properties were studied in detail as a function of the hybrid material incorporated through X-Ray Diffraction (XRD), Thermogravimetric (TG) and Differential Scanning Calorimetry (DSC), Scanning Electronic Microscopy (SEM), Fourier transform infrared Spectroscopy (FT-IR) whereas the parameters of tensile strength and elongation at break from stress vs strain curves allowed to know the mechanical properties of the composite films. The conventional and exfoliated composites were obtained as consequence of the good dispersion and interaction through the H-bonds networks between the hybrid materials and polymer matrix due to the presence of the polar functional groups as –OH groups of the polymer, the crystallization water molecules, adsorbed water molecules and OH groups of phenolic acids in the hybrid materials. The good dispersion and interaction of the hybrid material and polymer matrix is supported with the reduction of the crystallinity on the composite films respect to that of the pure PVA films, which were obtained from DSC curves during the heating process. The estimated tensile strength evidenced an improvement of this parameter on the composite films with low content of filler (%w) in comparison with those values of the pure PVA films. The good dispersion of layered structure in the polymer matrix leads to an increase of stiffness of the composite films giving rise to the better response. The composite films from PVOH/Hybrid materials employed for the strawberries packaging during six days of storage under temperature and relative humidity conditions of relative humidity 17.3± 1 °C and 66 ± 2 % evidenced a positive effect on appearance, firmness retention and loss weight in comparison with those strawberries packaged in pure PVA films. Thus, the PVA/hybrid materials showed a beneficial effect on the conservation of strawberry quality in comparison with the pure PVA films that convert them in a promising option in food packaging with bioactivity properties.<br